Polyphosphate Dynamics in Cable Bacteria - Geerlings, Nicole M. J.; Kienhuis, Michiel V. M.; Hidalgo-Martinez, Silvia; Hageman, Renee; Vasquez-Cardenas, Diana; Middelburg, Jack J.; Meysman, Filip J. R.; Polerecky, Lubos (Frontiers in Microbiology, 2022)
Cable bacteria are multicellular sulphide oxidizing bacteria that display a unique metabolism based on long-distance electron transport. Cells in deeper sediment layers perform the sulphide oxidizing half-reaction whereas cells in the surface layers of the sediment perform the oxygen-reducing half-reaction. These half-reactions are coupled via electron transport through a conductive fibre network that runs along the shared cell envelope. Remarkably, only the sulphide oxidizing half-reaction is coupled to biosynthesis and growth whereas the oxygen reducing half-reaction serves to rapidly remove electrons from the conductive fibre network and is not coupled to energy generation and growth. Cells residing in the oxic zone are believed to (temporarily) rely on storage compounds of which polyphosphate (poly-P) is prominently present in cable bacteria. Here we investigate the role of poly-P in the metabolism of cable bacteria within the different redox environments. To this end, we combined nanoscale secondary ion mass spectrometry with dual-stable isotope probing (13C-DIC and 18O-H2O) to visualize the relationship between growth in the cytoplasm (13C-enrichment) and poly-P activity (18O-enrichment). We found that poly-P was synthesized in almost all cells, as indicated by 18O enrichment of poly-P granules. Hence, poly-P must have an important function in the metabolism of cable bacteria. Within the oxic zone of the sediment, where little growth is observed, 18O enrichment in poly-P granules was significantly lower than in the suboxic zone. Thus, both growth and poly-P metabolism appear to be correlated to the redox environment. However, the poly-P metabolism is not coupled to growth in cable bacteria, as many filaments from the suboxic zone showed poly-P activity but did not grow. We hypothesize that within the oxic zone, poly-P is used to protect the cells against oxidative stress and/or as a resource to support motility, while within the suboxic zone, poly-P is involved in the metabolic regulation before cells enter a non-growing stage.